Measuring Procedural Knowledge in Problem Solving Environments with Item Response Theory - Hernando, Manuel; Guzmán-de-los-Riscos, Eduardo Francisco; Conejo-Muñoz, Ricardo José (Springer, 2013)
In this paper, a new data-driven model to measure procedural knowledge is described. The model is based on Item Response Theory. The main idea behind this new model is to establish an analogy between the testing and the problem solving environment. For this purpose, we model each problem (or exercise) solution path as a directed graph where nodes are states of the problem and edges, transitions between states (i.e. the actions accomplished by the student). We can match this model with testing by seeing each node as a question and each edge as choices within the questions.
Keywords: Resolución de problemas - Proceso de datos; Problem solving environments; Student modeling; Procedural knowledge estimate; Item Response Theory